Avaliação pré-natal dos defeitos de fechamento da parede corporal anterior por ressonância magnética - Braga, Fernanda Del Campo Braojos (2016)
Background - Closing defects of the anterior body wall consists of a large group of congenital anomalies characterized by herniation of one or more viscera to the amniotic cavity by a ventral hole, with an incidence of one in 2,000 live births. Malformations included in this group are gastroschisis, omphalocele, ectopia cordis and Pentalogy of Cantrell, limb-body wall complex and bladder/cloacal extrophy. The common origin of the body closing failures, except omphalocele, is based on an unifying embryological hypothesis, in which the defects are the consequences of a failure in the process of fusion between the two lateral body folds. To understand this mechanism is necessary a comprehension of the formation of folds of the body wall. Objectives - To characterize the body wall closure defects in fetuses by MRI and to evaluate the MRI contribution as a method complementary to ultrasonography in indication of surgical method. Patients and Methods - This is a longitudinal/ prospective study comprinsing 31 pregnant women with fetuses diagnosed with anterior body wall closure defects distributed in: Group 1 (G1) - pregnant women in medical care at the Base Hospital ( HB / FAMERP ) in the period from January 2009 to July 2014; Group 2 (G2 ) - pregnant women in medical care at the HB / FAMERP from September 2014 to December 2015. Gastroschisis, omphalocele, ectopia cordis, Pentalogy Cantrell, limb-body wall complex, and bladder exstrophy were included among these defects. Results - The evaluation of fetal MRI allowed the anatomic - morphological characterization of the conceptus and of the anterior body wall defect regarding to its location, extent and herniated contents and detection of birth defects associated with the diagnosis of anterior body wall defect. Conclusion - The understanding of embryonic development as a dynamic process is essential in characterizing the closure defects of the anterior body wall on MRI, reflecting the accuracy of diagnosis and, consequently, the course of pregnancy and planning of surgical treatment. In addition, the excellent spatial resolution of MRI and spontaneous contrast of structures help in detecting other associated malformations and complications of the evolution of body closure defects. Thus, MRI contributes to the preparation of family and multidisciplinary hospital staff.